INFORMALITY AS POLITENESS STRATEGIES IN REQUEST OF ENGLISH EDUCATION STUDY PROGRAM OF RIAU ISLANDS UNIVERSITY - Suswanto Ismadi Megah (Universitas Riau Kepulauan, 2017)
This study was aimed to identify the informality of request as politeness strategies used by the students of English Education study Program (English department) of Unrika Batam.The data was obtained from request spoken by the student of English department students. The data taken based on cluster sampling due the homogeneous data. The data was students of morning class of semester seven. This study concluded that The usage of bu, ma, mah (means mother) five data and yah, pak, and pa (means father or daddy), the speaker respects to the hearer’s face by addressing her as mom. This considered her position is upper position; this does not threaten her face. This is used informally to her mother in relaxed situation. The usage of imperative sentences are four data when the hearer asks her young sister to take the glass, then the subject asks her big sister to buy her dress, when she asks her young sister to take chilly and when the subject ask the money to pay rental house. This sentences forces her face’s hearer. This shows negative face. The last is speaker states “adek” young sister to her father means to soften request to her father due to the father will usually fulfill the young child.